Analisis faktor peringkat kedua terhadap prinsip-prinsip pengurusan kualiti - Lim, Kong Teong; Tang, Swee Mei (Universiti Utara Malaysia, 2008)
This empirical study uses second-order factor analysis to test whether a set of quality management principles, synthesised from quality gurus’ philosophies and prominent quality award and quality management system frameworks, together constitute a higher-order factor that may be termed Total Quality Management (TQM). Using survey data collected from educational departments selected randomly from 10 public universities in Malaysia, the LISREL 8 computer program (Jöreskog & Sörbom, 1993) was used to estimate and evaluate the goodness of fit of the proposed second order factor model. The results indicated that the proposed model fits the data adequately, and support the existence of second-order relationship among the quality management principles, adequately, and support the existence of second-order relationship among the quality management principles.